PERSEPSI LURAH TENTANG KETERLIBATAN AYAH DALAM PENGASUHAN DAN PENDIDIKAN ANAK USIA DINI - Beatriks Novianti Kiling-Bunga; Yohana Krista Eka Tafuli; Friandry Windisany Thoomaszen; Indra Yohanes Kiling (Direktorat Pembinaan Guru dan Tenaga Kependidikan Pendidikan Anak Usia Dini Kementerian Pendidikan dan Kebudayaan bekerjasama dengan Fakultas Ilmu Pendidikan Universitas Negeri Jakarta, 2017)
Father’s involvement in parenting and early childhood education and development (ECED) is a form of active participation in supporting child’s development. Father does not often actively participated in parenting particularly in the community having patrilinial system. The study, conducted from October 2015 to March 2016 in Kupang, aimes at identifying father’s involvement in parenting and ECE. Research design used was qualitative with interview as data collection method. Four heads of urban community participated in this reseatch. Thematic analysis was conducted.The result of the study indicates that fathers in Kupang city have involved themselves in parenting and ECED, but the involvement are limited to economic needs fulfillment while attention and emotional needs are less fulfilled. The study suggests to improve father’s involvement through socializations, seminars or discussions.